2017
DOI: 10.1007/s00049-017-0242-4
|View full text |Cite
|
Sign up to set email alerts
|

Methyl N-methylanthranilate: major compound in the defensive secretion of Typhloiulus orpheus (Diplopoda, Julida)

Abstract: The defensive secretion of the julid diplopod Typhloiulus orpheus contains methyl N-methylanthranilate (MNMA), an ester of N-methylanthranilic acid that comprises more than 99% of secretion of this species. MNMA is accompanied by small amounts of methyl anthranilate and two benzoquinones (2-methyl-1,4-benzoquinone and 2-ethyl-1,4-benzoquinone, respectively). MNMA is a known intermediate in the biosynthesis of both benzoquinones (as present in defensive secretions of juliformians) and glomerin-like quinazolines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Members of the order Julida, together with spirostreptidans and spirobolidans, are traditionally classified as belonging to the category of “quinone millipedes” [ sensu Eisner, Alsop, Hicks, and Meinwald ()] because the most prominent compounds of their defensive secretion are quinones. Apart from quinones, defensive gland exudates of julidans can contain phenolics, alcohols, aldehydes, esters and anthranilate derivatives (Bodner & Raspotnig, ; Bodner, Vagalinski, Makarov, & Raspotnig, ; Bodner et al., ; Huth, ; Makarov et al., ; Sekulić et al., ; Vujisić et al., ; Wheaterston, Tyrell, & Percy, ; Wheeler, Meinwald, Hurst, & Eisner, ). The typical julidan defensive secretion is a blend of benzoquinones (as dominant compounds) and some of the mentioned compounds, but there are species within this order with an aberrant chemoprofile of defence compounds (Bodner et al., , ; Shimizu, Kuwahara, Yakamuru, & Tanabe, ).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the order Julida, together with spirostreptidans and spirobolidans, are traditionally classified as belonging to the category of “quinone millipedes” [ sensu Eisner, Alsop, Hicks, and Meinwald ()] because the most prominent compounds of their defensive secretion are quinones. Apart from quinones, defensive gland exudates of julidans can contain phenolics, alcohols, aldehydes, esters and anthranilate derivatives (Bodner & Raspotnig, ; Bodner, Vagalinski, Makarov, & Raspotnig, ; Bodner et al., ; Huth, ; Makarov et al., ; Sekulić et al., ; Vujisić et al., ; Wheaterston, Tyrell, & Percy, ; Wheeler, Meinwald, Hurst, & Eisner, ). The typical julidan defensive secretion is a blend of benzoquinones (as dominant compounds) and some of the mentioned compounds, but there are species within this order with an aberrant chemoprofile of defence compounds (Bodner et al., , ; Shimizu, Kuwahara, Yakamuru, & Tanabe, ).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile an impressive chemical repertoire has been reported from different millipede orders, including various quinones, esters, alcohols, cyanogenic compounds and unusual aromatic alkaloids (Shear, 2015;Bodner et al, 2018). Alkaloids arewith a few exceptions (Bodner et al, 2017) mainly found in the secretions of two groups of diplopods, Glomerida and Colobognatha. The chemistry of Glomerida appears to be predominated by two unique quinazoline alkaloids: glomerin and homoglomerin (Meinwald et al, 1966;Shear et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…One of the hallmarks of the millipede order Julida (as well as their closest relatives Spirobolida and Spirostreptida) is the synthesis of quinone-based defensive secretions [1417]. Exudates of julidan defensive glands are cocktails made of different compounds–benzoquinones, phenolics, alcohols, aldehydes, esters, anthranilate derivatives, and ketones ([16] and references therein).…”
Section: Introductionmentioning
confidence: 99%